2017
DOI: 10.1121/1.4994288
|View full text |Cite
|
Sign up to set email alerts
|

Corpus of deaf speech for acoustic and speech production research

Abstract: A corpus of recordings of deaf speech is introduced. Adults who were pre- or post-lingually deafened as well as those with normal hearing read standardized speech passages totaling 11 h of .wav recordings. Preliminary acoustic analyses are included to provide a glimpse of the kinds of analyses that can be conducted with this corpus of recordings. Long term average speech spectra as well as spectral moment analyses provide considerable insight into differences observed in the speech of talkers judged to have lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Other two spectral moments (spectral mean and skewness) indicated that those with highly intelligible speech yields more energy in the high-frequency. This findings were in line with Raghavendra et al, [15] in which they systematically analyzed the /s/, /ʃ/, /f/, and /θ/ of the same dataset in Mendel et al, [14] by cutting them as a short duration of fricative segments.…”
Section: Spectral Moment Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Other two spectral moments (spectral mean and skewness) indicated that those with highly intelligible speech yields more energy in the high-frequency. This findings were in line with Raghavendra et al, [15] in which they systematically analyzed the /s/, /ʃ/, /f/, and /θ/ of the same dataset in Mendel et al, [14] by cutting them as a short duration of fricative segments.…”
Section: Spectral Moment Analysissupporting
confidence: 89%
“…Recently, Mendel et al [14] analyzed four spectral moments (spectral mean, standard deviation, skewness, and kurtosis) for short passages spoken by three hearing impaired groups that were sorted based on perceptual intelligibility. In the results, spectral variance (standard deviation) increased with increases in intelligibility, while kurtosis decreased with increases in intelligibility, suggesting that speech that is more intelligible has a broader range of frequency distribution.…”
Section: Spectral Moment Analysismentioning
confidence: 99%
“…Two groups of 8 talkers each were selected from the “Corpus of deaf speech for acoustic and speech production research” database collected at the University of Memphis ( Mendel et al, 2017 ). This corpus is a pool of speech recordings digitally sampled at 44,100 Hz, spoken by NH talkers and hearing impaired (HI) talkers.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 presents the demographic details of the chosen CI talkers from the database ( Mendel et al, 2017 ). The CI talkers are aged between 16 and 77 years with an average age of 47.5 years.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the mean spectral energy of CI patients is lower than that of normal individuals, implying that they have difficulty in pronouncing high-frequency words. Patients with CI also pause (staccato) in the middle of the speech and often confuse voiceless with voiced speech [6,7]. The characteristics of CI patients' speech differ from those of standard speech.…”
Section: Introductionmentioning
confidence: 99%